Studi Tingkat Keterampilan Berpikir Kritis Siswa Pada Materi Bentuk Aljabar Kelas VII Di SMPN 1 Narmada - Azwina Amalia; Ketut Sarjana; Baidowi Baidowi; Arjudin Arjudin (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aimed to describe the level of critical thinking skills in Year 7 students of SMPN 1 Narmada related to the subject of Algebra. This study was quantitative descriptive. The instruments of this study implemented the indicators based on Perkins and Murphy’s levels of critical thinking skills, which are (1) clarification, (2) assessment, (3) strategy, and (4) inference. There were 352 students in this study population with 64 students as the samples were obtained with a simple random sampling technique. Written test and interview was applied as the data collection technique with descriptive statistics as the data analysis technique. The results showed that 4,69% of the students grouped as having a high level of critical thinking skills had already had the ability to answer all questions completing all stages of critical thinking skills. While 4,69% of the students categorized as having the middle level had answered the questions using their level of critical thinking skill except for numbers 3 and 4 leaving some incompleted stages of critical thinking skill. Significantly, 90,62% of the students categorized as low level were not able to answer the questions with the stages of critical thinking skills. This concluded that the level of critical thinking skills on the subject of Algebra in Year 7 students of SMPN 1 Narmada is low categorized.